Synthesis and Microwave Absorbing Properties of Porous One-Dimensional Nickel Sulfide Nanostructures - Lu, Min; Wu, Qian; Guan, Xiao-Hui; Xu, Wei; Zhang, Hao-Yue; Di, Xin; Wang, Guang-Sheng; Dong, Shao-Hua (Frontiers in Chemistry, 2018)
One-dimensional (1D) porous NixSy nanostructures have been successfully fabricated by two-step method consisting of solvothermal and subsequent annealing process. The suitable heat treatment temperature and reaction time play crucial roles in the final structure, morphology, as well as performance. The uniform and perfect porous NixSy nanostructures obtained at 310 °C exhibit outstanding microwave absorption performances. A minimum reflection loss of −35.6 dB is achieved at 8.5 GHz, and the effective absorption bandwidth almost covers 14.5 GHz with the absorber thickness range of 2.0−5.0 mm. It can be supposed that this porous structure with rough surface which is favor for increasing the microwave multiple reflection and scattering, contributes a high-performance electromagnetic absorption.